Islam dan Filsafat Perenial: Respon Seyyed Hossein Nasr terhadap Nestapa Manusia Modern - Fathin Fauhatun (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This paper examines Seyyed Hossein Nasr's thoughts on Islam and perennial philosophy in dealing with the problems of modern humans. The purpose of this article is to explain the plight of modern humans and to explain how to overcome this problem through a study of the thoughts of a contemporary Muslim figure, namely Seyyed Hossein Nasr. In Nasr's perspective, perennial philosophy is a philosophy of eternity which is also interpreted as traditional wisdom. This thought about Nasr's perennial philosophy emerged as a critical reaction to what he saw as a crisis in modern humans. Modern civilization in the West which also flourished in the Islamic world, according to Nasr, has failed to achieve its goals because it has caused a variety of existentialism and spiritual crises experienced by modern humans. Through perennial philosophy, Nasr explained that to deal with the problems currently faced by modern humans is to get closer to God through Sufism as has been done by ancient scholars.